Bagets Viva Film Production ; directed by Maryo J. Delos Reyes. - Delos Reyes, Mario; Martinez, William; Bonnin, JC; Lauchengco, Raymond; Muhlach, Aga; Bautista, Herbert (Viva Films Production, 1999)
In an age when life confuses more than it explains, five teenage boys come together and vow to uncover life's mysteries and conquer the world. Their backgrounds are as disparate as their preference, but their friendship goes beyond things superficial. A witty, light- hearted coming of age, move about the joys and paints of growing up in these turbulent times.